HUBUNGAN KEEFEKTIFAN PEMBINAAN DAN PENGEMBANGAN KEPROFESIAN BERKELANJUTAN DENGAN KINERJA GURU DALAM PEMBELAJARAN SMKN DI KOTA MALANG - Mutya Alfarina; Djum Djum Noor Benty; Desi Eri Kusumaningrum (Universitas Negeri Malang, 2019)
Abstract: the goal of this research was to know: (1) the level effectiveness of teachers’ coaching events in all vocational high schools in Malang City; (2) the effective level of sustainable professionalism at vocational high schools Malang City; (3) the level teachers’ teaching performance at vocational high schools Malang City; (4) the correlation between coaching and teachers’ teaching performance at vocational high schools Malang City; (5) the correlation between development of sustainable professionalism and teachers’ teaching performance at vocational high schools Malang City; and (6) the correlation between coaching and development of sustainable professionalism with teachers’ teaching performance at vocational high schools. This research used quantitative approach with using correlational descriptive design. Based on analysis data, there were six conclusions as followed: (1) the level effectiveness of teachers’ coaching in all vocational high schools in Malang City was in moderate category; (2) the level effectiveness development of sustainable professionalism (DSP) in all vocational high schools in Malang City was in low category; (3) the level of teachers’ performance for learning in all vocational high schools in Malang City was high category; (4) there was no relationship significantly between effectiveness of coaching and using teachers’ performance in all vocational high schools in Malang City; (5) there was low relationship between development of sustainable professionalism and teachers’ performance for learning development of sustainable professionalism in all vocational high schools in Malang City; and (6) there was low relationship coaching and development of sustainable professionalism using teachers’ performance for learning. Keyword: Coaching; development of sustainable professionalism; teachers’ teaching performance Abstrak: Penelitian ini dilaksanakan dengan tujuan untuk mengetahui: (1) tingkat keefektifan kegiatan pembinaan guru SMKN di Kota Malang; (2) tingkat keefektifan kegiatan pengembangan profesi guru berkelanjutan SMKN di Kota Malang; (3) tingkat kinerja guru dalam pembelajaran SMKN di Kota Malang; (4) hubungan antara keefektifan pembinaan dan kinerja guru dalam pembelajaraan SMKN di Kota Malang; (5) hubungan antara pengembangan keprofesian berkelanjutan dan kinerja guru dalam pembelajaran SMKN di Kota Malang; dan (6) hubungan keefektifan pembinaan dan pengembangan keprofesian berkelanjutan dengan kinerja guru dalam pembelajaran SMKN di Kota Malang. Penelitian ini menggunakan pendekatan kuantitatif dengan rancangan penelitian bersifat deskriptif korelasional. Kesimpulan dari penelitian adalah: (1) tingkat keefektifan pembinaan guru SMKN di Kota Malang masuk dalam tingkatan kategori sedang; (2) tingkat keefektifan pengembangan keprofesian berkelanjutan (PKB) guru SMKN di Kota Malang masuk dalam tingkatan kategori rendah; (3) tingkat kinerja guru dalam pembelajaran SMKN di Kota Malang masuk dalam tingkatan kategori tinggi; (4) tidak ada hubungan yang signifikan antara keefektifan pembinaan dengan kinerja guru SMKN di Kota Malang; (5) ada hubungan rendah antara pengembangan keprofesian berkelanjutan (PKB) dengan kinerja guru dalam pembelajaran SMKN di Kota Malang; dan (6) ada hubungan sangat rendah keefektifan pembinaan dan pengembangan keprofesian berkelanjutan (PKB) dengan kinerja guru dalam pembelajaran. Kata Kunci: pembinaan; pengembangan keprofesian berkelanjutan; kinerja guru dalam pembelajaran